Precedent Names as a Part of the Polish Text in Russian Poetry - Воронцова, Кристина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The author analyses the structure and components of the ‘Polish text’ in the Russian literature after the Second World War. One of the main aspects of this phenomenon is the so-called precedent name. This can be observed when the image of a person (real or fictional) becomes a cultural text or myth. For the ‘Polish text’ in Russian literature such significant names have been Adam Mickiewicz, Julian Tuwim, Juliusz Słowacki, Czesław Miłosz and Konstanty Ildefons Gałczyński. In the Russian mentality Poland has always evoked poetry in general, which means that characteristics of ‘the Polish text’ can be identified through an analysis of poems about these cultural figures.